Developing generic tools for characterizing agricultural systems for climate and global change studies - Rufino, Mariana C.; Quiros, Carlos; Boureima, Moussa; Desta, Solomon; Douxchamps, Sabine; Herrero, Mario; Kiplimo, Jusper; Lamissa, Dikite; Mango, Joash; Moussa, Abdoulaye S.; Naab, Jesse; Ndour, Yacine; et al. (CCAFS, 2013)
Standard methods are needed to collect data to evaluate the performance of agricultural systems. Standardization allows comparisons across systems, and potentially the extrapolation of recommendations to similar development domains. The Integrated Modelling Platform for Mixed Animal Crop Systems (IMPACT, Herrero et al., 2007) is a data collection protocol and computer software tool designed to gather minimum datasets in smallholder crop-livestock systems. The protocol collects information ranging from household composition to crop and livestock production to household food consumption and household assets. Although IMPACTS’s datasets are detailed to conduct a wide range of crop-livestock systems analysis, the data collection on the field proved to be time and resources demanding. The protocol works in monthly time steps i.e., most of the data is collected per month, thus it takes considerable time to complete an interview. The printed forms comprise over 30 different templates that resemble the screens in the software, and although this could speed up data entry, its use on the field for data collection often tends to be inoperative. In 2011 CCAFS commissioned to ILRI the task of assessing the possibilities for simplifying IMPACT to carry out a characterization across the 15 CCAFS benchmark sites (Table 1). The objective of this project called ‘IMPACTlite’ was to modify IMPACT to be able to collect household-level data detailed enough to capture within-site variability on key performance and livelihood indicators that could be used for a range of analysis including the modelling of impact of adaptation and mitigation strategies on livelihoods, food security and the environment. A team composed of agronomists, economists, computer, environmental, and social scientists modified and tested the new tool in a number of sites. The changes implemented to the tool are reported in Quiros et al. (2011). In this report we describe the steps undertaken in the implementation of the surveys using IMPACTlite in the IGPs, the progress achieved, and next steps planned for 2013.